Ekuitas Merek ditinjau dari Brand Awareness, Brand Association, dan Perceived Quality (Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to examine and analyze the influence of brand awareness, brand association, and perceived quality on the brand equity of Sariayu Martha Tilaar with a case study in this research, namely students of IAIN Kudus class of 2019. This type of research is field research which uses a quantitative approach with analytical methods multiple linear regression. The samples in this study were 326 respondents with a sampling approach using purposive sampling. The technique used to carry out the analysis is using validity test, reliability test, classical assumption test, multiple linear analysis, hypothesis testing consisting of partial t test, simultaneous f test, and test of the coefficient of determination with the help of the SPSS 20 software program. The results of this study show that there is a positive and significant influence between brand awareness on brand equity with a total value of t count greater than t table (2,613 > 1,967), meaning that with brand awareness in the minds of consumers, brand equity can further increase. Brand association has a positive and significant effect on brand equity with a calculated t value greater than t table (5,556 > 1,967), meaning that with a strong brand association on a brand, it will be able to create and increase brand equity. positive and significant to brand equity with a calculated t value greater than t table (8,017 > 1,967), meaning that the existence of good perceived quality of a brand can also increase brand equity.Keywords: Brand Equity, Brand Awareness, Brand Association, Perceived Quality